Case reportCross-reaction to quail’s egg and ostrich egg in 6-year-old boy sensitized to hen’s egg – a case report - Nowacki, Zygmunt; Mika, Maria (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Cross-reaction with food allergens is a common clinical problem. The paper describes a case of a 6-year-old boy with atopic dermatitis, asthma, allergic rhinitis and epilepsy, sensitized to hen’s egg, in whom cross-reaction was observed after ingestion of quail eggs and ostrich eggs. Through the first four months of life he was breast fed with supplementation of modified milk and in the second month of life experienced symptoms of atopic dermatitis. Hen’s egg and chicken meat were not included in the child’s diet. In the fifteenth month of life a few minutes after eating boiled quail eggs he developed hives and started vomiting. In the sixth year of life he developed urticaria immediately after eating an omelette made from ostrich eggs. Cross-allergy is difficult to predict and its diagnosis is a very complex process which should be done in a stepwise manner. The diagnostic work-up, in addition to the interview and physical examination, includes a number of studies conducted both in vivo and in vitro . When setting up a diet for a patient with IgE-mediated allergies one should particularly note the phylogenetic relationships between the different species of animals. A change in eating habits is associated with increased risk of the cross-allergy phenomenon.